(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
The information on the commercial exchange of agri-food goods that takes place in Mexico is compiled through the National Institute of Statistics and Geography (INEGI) which registers the Foreign Trade Statistics of Mexico (ECEM), whose information allows decision-making in commercial matters and financial. However, a method has not been developed to validate the imported and exported volume data of commercial operations through a customs agent, so there is an over-registration of the data. Therefore, the proposal to establish a validation method for agri-food imports and exports considering the volumes by tariff fraction and unit of measure, as well as the incoterms, to generate a specific record will allow obtaining more reliable information, which will be of interest to the decision-making of the actors involved in foreign trade.